'It is men who die and all that, so what is new?' Male vulnerability, institutionalised masculinity and the present absence of a problem in Swedish rescue service accident prevention. Issue 3 (3rd July 2021) - Ericson, Mathias
ABSTRACT: Men die in accidents more frequently than women. However, the statistical facts do not necessarily translate into any self-evident discussion of addressing men and masculinity construction in work with accident prevention. This article draws upon theories of masculinity, affect and haunting in order to discuss social and institutional processes that support a gender-neutral approach to accidents, where the high frequency of men is just something you accept. The analyses are based on observations and interviews with people who work with accident investigation and prevention within the rescue service in Sweden. The article suggests that male vulnerability is reiterated as a haunting phenomenon beyond the responsibility of the rescue service which reproduces masculinity as a form of cruel optimism.